Impact of Balloon Guide Catheter Use on Clinical and Angiographic Outcomes in the STRATIS Stroke Thrombectomy Registry. Issue 3 (March 2019) - Zaidat, Osama O.; Mueller-Kronast, Nils H.; Hassan, Ameer E.; Haussen, Diogo C.; Jadhav, Ashutosh P.; Froehler, Michael T.; Jahan, Reza; Ali Aziz-Sultan, Mohammad; Klucznik, Richard P.; Saver, Jeffrey L.; Hellinger, Frank R.; Yavagal, Dileep R.; et al.
Abstract : Background and Purpose—: Mechanical thrombectomy has been shown to improve clinical outcomes in patients with acute ischemic stroke. However, the impact of balloon guide catheter (BGC) use is not well established. Methods—: STRATIS (Systematic Evaluation of Patients Treated With Neurothrombectomy Devices for Acute Ischemic Stroke) was a prospective, multicenter study of patients with large vessel occlusion treated with the Solitaire stent retriever as first-line therapy. In this study, an independent core laboratory, blinded to the clinical outcomes, reviewed all procedures and angiographic data to classify procedural technique, target clot location, recanalization after each pass, and determine the number of stent retriever passes. The primary clinical end point was functional independence (modified Rankin Scale, 0–2) at 3 months as determined on-site, and the angiographic end point was first-pass effect (FPE) success rate from a single device attempt (modified Thrombolysis in Cerebral Infarction, ≥2c) as determined by a core laboratory. Achieving modified FPE (modified Thrombolysis in Cerebral Infarction, ≥2b) was also assessed. Comparisons of clinical outcomes were made between groups and adjusted for baseline and procedural characteristics. All participating centers received institutional review board approval from their respective institutions. Results—: Adjunctive technique groups included BGC (n=445), distal access catheter (n=238), and conventional guide catheter (n=62). The BGC group had a higher rate of FPE following first pass (212/443 [48%]) versus conventional guide catheter (16/62 [26%]; P =0.001) and distal access catheter (83/235 [35%]; P =0.002). Similarly, the BGC group had a higher rate of modified FPE (294/443 [66%]) versus conventional guide catheter (26/62 [42%]; P <0.001) and distal access catheter (129/234 [55%]; P =0.003). The BGC group achieved the highest rate of functional independence (253/415 [61%]) versus conventional guide catheter (23/55 [42%]; P =0.007) and distal access catheter (113/218 [52%]; P =0.027). Final revascularization and mortality rates did not differ across the groups. Conclusions—: BGC use was an independent predictor of FPE, modified FPE, and functional independence, suggesting that its routine use may improve the rates of early revascularization success and good clinical outcomes. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02239640. Abstract : Supplemental Digital Content is available in the text.